TINJAUAN YURIDIS TENTANG PENYELESAIAN SENGKETA PERBANKAN MELALUI LEMBAGA MEDIASI - Mang Surast Suthawijaya (LEGAL OPINION, 2024)
The results of the study revealed that the legal position of banking mediation in non-litigation dispute resolution has been implemented in accordance with the provisions of the law but in its implementation it has not been running effectively, this is because the Bank of Indonesia has not disclosed information to customers regarding the settlement of complaints and the authority of customers in relation to banking mediation, in addition, The implementation of banking mediation can be carried out if it has a unit or institution that has the authority to resolve disputes or conflicts between customers and banks, then related to the implementation of legal decisions between problematic parties, it is necessary to have a clear peace agreement that binds both parties, both the customer and the bank, because the agreement that occurs between the parties is an agreement based on good faith that one party may not agree. ABSTRAK Hasil penelitian mengungkapkan bahwa kedudukan hukum mediasi perbankan dalam penyelesaian sengketa non litigasi, sudah dilaksanakan sesuai ketentuan aturan hukum tetapi di dalam pelaksanaannya belum berjalan secara efektif hal ini di sebabkan belum terbukanya informasi dari pihak Bank Indonesia terhadap nasabah menyangkut penyelesaian pengaduan maupun kewenanga n nasabah dalam kaitannya dengan mediasi perbankan, di samping itu, pelaksanaan mediasi perbankan dapat di laksanakan apabila memiliki unit atau lembaga yang mempunyai kewenangan untuk menyelesaiakan sengketa atau konflik antara nasabah dengan pihak bank, kemudian terkait dengan pelaksanaan putusan hukum antara para pihak yang bermasalah.